2015
DOI: 10.1097/mrr.0000000000000103
|View full text |Cite
|
Sign up to set email alerts
|

Effects of therapeutic Tai Chi on balance, gait, and quality of life in chronic stroke patients

Abstract: The aim of this study was to analyze the effects of therapeutic Tai Chi on balance, gait, and quality of life in chronic stroke patients. Twenty-two inpatients diagnosed with stroke were divided randomly into two groups: one treated with both general physical therapy and Tai Chi exercise (11 patients) and one treated with only general physical therapy (11 patients). Therapeutic Tai Chi included 10 different movements and was performed for 60 min, twice per week, for 6 weeks. Pretest and post-test measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 23 publications
3
70
0
4
Order By: Relevance
“…On the other hand, once their abilities permitted it, participants were encouraged to practice upper limb movements both together and to coordinate these with lower limb movements in standing positions. The participants who used standing positions improved their balance following the intervention subjectively, which is consistent with other studies that have reported Tai Chi benefits for balance training post stroke [14][15][16]. Therefore, this study provided also an intervention using whole body rehabilitation for stroke survivors with sufficient balance.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…On the other hand, once their abilities permitted it, participants were encouraged to practice upper limb movements both together and to coordinate these with lower limb movements in standing positions. The participants who used standing positions improved their balance following the intervention subjectively, which is consistent with other studies that have reported Tai Chi benefits for balance training post stroke [14][15][16]. Therefore, this study provided also an intervention using whole body rehabilitation for stroke survivors with sufficient balance.…”
Section: Discussionsupporting
confidence: 77%
“…Through consistent weight shifting between two feet [10], Tai Chi has been broadly reported as beneficial for improving balance and for fall prevention in the elderly [11][12][13]. Recently, there is some evidence supporting its benefits in improving balance in chronic stroke patients [14][15][16]. However, its use for upper limb rehabilitation remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have suggested that tai chi has favourable effects on a variety of factors, including cardiovascular protection (10), fall prevention (11), balance (12), flexibility (13), depression (14) and quality of life (QoL) (15). Tai chi has potential benefits in treating different diseases, including chronic obstructive pulmonary disease (16), Parkinson's disease (17), osteoarthritis (18) and stroke (19). Thus, tai chi may be a suitable exercise for individuals with chronic diseases (9,20).…”
Section: Data Sourcesmentioning
confidence: 99%
“…, and 2 studies did not document the practice style (14,15). All of the studies aimed to examine the effectiveness of tai chi on standing balance and gait ability of stroke survivors.…”
Section: )mentioning
confidence: 99%
“…Although the studies by Kim et al (15) and Au-Yeung et al (13) reported data on static standing balance, they used different outcome indicators and reported the results according to various test conditions; thus it was difficult and not robust to pool all of the data Similarly, the study by Au-Yeung et al (13) was not included in the pooled analysis for dynamic standing balance. However, there was no significant difference in dynamic standing balance between the tai chi and control groups (0.154 [-0.269 ~ 0.578], p = 0.475; I 2 = 26.6%, p = 0.256).…”
Section: Standing Balancementioning
confidence: 99%